Informal trade and the price of import bans: Evidence from Nigeria - Bensassi, Sami; Jarreau, Joachim; Mitaritonna, Cristina (International Food Policy Research Institute, 2016)
This paper studies the impact of trade restrictions and illegal trade on price disparities within Nigeria, where a long list of import prohibitions on various consumer goods have raised the price of the consumption basket. Large-scale illegal trade at the border with Benin allows traders bypass these prohibitions. We investigate whether this illegal trade mitigates the impact of import bans on domestic prices. Using a simple theoretical model and monthly price data, we exploit changes in the prohibition list, as well as spatial variation between border and non-border states, to identify the effect of smuggling. Results indicate that, for agricultural goods in particular, the price hike associated with an import ban is lower in border states. However, we find little evidence that bans disrupt the cointegration relationship between states. These results are consistent with a large diffusion of smuggled goods across Nigerian states, and with the higher price elasticity to distance in the illegal trade sector.